2019
DOI: 10.1088/1755-1315/365/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Study on Physical characteristics of Pliek U: comparisons among fermentation stages

Abstract: Pliek u is most popular food product in Aceh province, made from fermented coconut. There are three derivative products produced from the fermentation process, namely simplah oil, Pliek oil and Pliek U. Prior to be processed, size reduction is performed by means of grating instrument and thus, fermentation is begun. The main purpose of this present work is to systematically study the physical characteristics and compares the effect of fermentation stages to temperature and pH changes. Randomized Complete Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, the moisture of pliek-u produced by treatment P2 was not significantly different from the moisture of pliek-u produced by treatment P1 (combination of 30% over mature and 70% mature). In contrast, the moisture of pliek-u produced in previous study was much lower in range of 4.4 to 6.4% [15]; 8.3 to 9.4% [17]; and 1.8 to 12.8% [20]. This lower moisture could be achieved as the use of solar tunnel dryer type Hohenheim Aceh.…”
Section: The Moisture Of Pliek-umentioning
confidence: 66%
See 2 more Smart Citations
“…However, the moisture of pliek-u produced by treatment P2 was not significantly different from the moisture of pliek-u produced by treatment P1 (combination of 30% over mature and 70% mature). In contrast, the moisture of pliek-u produced in previous study was much lower in range of 4.4 to 6.4% [15]; 8.3 to 9.4% [17]; and 1.8 to 12.8% [20]. This lower moisture could be achieved as the use of solar tunnel dryer type Hohenheim Aceh.…”
Section: The Moisture Of Pliek-umentioning
confidence: 66%
“…During the fermentation process, there were high metabolism of fungi and bacteria [3] that produce water and heat. Previous study had reported that the temperature of coconut during fermentation could reach about 39°C on the third day [17]. Different moisture of fermented coconut can be caused by different condition of this fermentation process.…”
Section: The Moisture Of Pliek-umentioning
confidence: 95%
See 1 more Smart Citation
“…Coconut (Cocos nucifera L.) is the most common cultivated plantation commodity in Indonesia, especially in Aceh Province. Usually, Aceh people process coconut flesh into three derivative products, namely pliek oil, simplah oil, and Pliek-U [1]. The Pliek-U production process consists of fermentation, drying, and pressing processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moisture content also determines the quality of Pliek-U samples. Water content is a parameter that affects the level of resistance of Pliek-U to damage due to high water content can cause by fungal and mold infections [1] The dregs produced from the pressing stage are called Pliek-U, which is often used as a spice for typical Acehnese dishes with a distinctive taste [5].…”
Section: Introductionmentioning
confidence: 99%